THE INFLUENCE OF THE GENIUS OF NIZAMI’S POETRY ON THE POEMS OF THE NEAR AND MIDDLE EAST - Umran Aliagha, Alizade Aliya (Collection of scientific papers «ΛΌГOΣ», 2024)
Nizami, who is the true sun of the horizon of Azerbaijani poetry of the XII century, illuminated the future development of poetry in the Near and Middle East, caused the birth of countless star galaxies in the vast sky of the world of wisdom due to the warm influence of the extraordinary heat of this poetic sun.